UPAYA MEMAKMURKAN MASJID DI TENGAH KEBERAGAMAN AGAMA KOTA MATARAM - Syaoki, Muhammad; Suswati, Rinda; Faizah, Faizah; Chakraborty, Swati (Fakultas Ushuluddin, Adab, dan Dakwah UIN Sultan Aji Muhammad Idris Samarinda, 2023)
The success of prospering the mosque cannot be separated from the mosque management strategy in prospering the mosque because the mosque management has an influence on the crowds of worshipers who come to worship at the mosque. The uniqueness found in the Al-Anwar mosque management in prospering the mosque that has built and tried to prosper the mosque in the midst of the diversity of the Mataram Youth Organization environment. namely by analyzing the environment then implementing strategic management and evaluating strategies so that it is a form of board effort in prospering the mosque. This research was designed with qualitative methods, data collection was carried out using interview techniques, observation and documentation. Data analysis procedures through the stages of data collection, data reduction, and data display conclusion drawing/verification. While the validity of this research data uses source triangulation and method triangulation. The results of this study are the strategy of the Al-Anwar mosque management in prospering the mosque in the midst of religious diversity in the Karang Taruna environment by continuing to carry out activity programs such as development activities, religious activities, worship activities, and educational activities from the programs that have been carried out are a form of the efforts of the Al-Anwar mosque management in prospering the mosque in the midst of religious diversity in the Karang Taruna Mataram environment.